The Ilocutionary Act of Joe Biden’s Speech Between Rusia and Ukraine - Bintang Chikar Hammada; Yenti Yenti; Putri Ayu Lestari (English Literature Department, Adab and Humanities Faculty, 2023)
This study discusses about the Illocutionary Act of Joe Biden Speech War between Rusia and Ukraine. The purposed of this study were to explain the types of illocutionary applied by Joe Biden in his speech. This study used a pragmatic approach from Leech (1989), Illocutionary Act from Searle (1999),and Leech (1993). The method used qualitative descriptive method to analyzed the data, the researcher used vidio and the script to collect the data, source of data was take from Joe Biden speech video. The findings of this study showed that (1) Joe Biden used five kinds of illocutionary act , they are Declarative, Directive, Expressive, Representative, and Commisive. Then, (2) there four function of illocutionary Act used by Joe Biden speech war, they are, Competitive, Collaborative, Convivial, and Conflictive